Waspada Anemia pada Lansia dengan Pemeriksaan Hemoglobin dan Hematokrit di Panti Werdha Hana - Ernawati Ernawati; Alexander Halim Santoso; Axsel Harsono; Anak Agung Ngurah Putrayoga Amertha (Pusat Riset dan Inovasi Nasional, 2025)
Anemia is a common hematological condition characterized by decreased hemoglobin levels or red blood cell counts, which affects the blood's capacity to transport oxygen throughout the body. In the elderly, anemia has a significant impact on health, such as decreased physical function, increased risk of falls, cognitive impairment, and increased health care costs. The global prevalence of anemia in the elderly is quite high, ranging from 5–10% at the age of 65–70 years and increasing to 15–25% at the age of over 80 years. The Community Service Program (PKM) at Panti Werdha Hana aims to increase awareness of the elderly regarding the importance of early detection of anemia. This activity uses the Plan-Do-Check-Act (PDCA) method, where hemoglobin and hematocrit levels are measured, and educational materials are provided regarding anemia and its risk factors. Respondents who have hemoglobin levels below normal are advised to seek further medical consultation. The results showed that 34 people (44.74%) had anemia and 42 people (55.26%) had normal hemoglobin levels. Early detection of anemia through hemoglobin and hematocrit examination is an important step in reducing the risk of more severe complications, so that it can improve the quality of life of the elderly.. Keywords: Anemia, Early Detection, Hemoglobin, Hematocrit